Development and characterization of a spleen cell line from yellowfin seabream Acanthopagrus latus and its susceptibility to Mandarinfish ranavirus - Zhipeng Zhan; Jiajie Fu; Huiquan Chen; Hongbo Pan; Shaoping Weng; Jianguo He; Changjun Guo (Journal of Fish Diseases, 2023)
Yellowfin seabream ( Acanthopagrus latus ) is one of the most commercially important marine fish in China. In this study, a new continuous cell line, named ALS cells, was developed from the spleen tissue of A. latus . The cell line was maintained in Dulbecco's modified Eagle medium/Nutrient Mixture F‐12 Ham (DMEM/F‐12) supplemented with 10% fetal bovine serum (FBS) and successfully cultured up to 50 passages. The cell line was authenticated by amplifying and sequencing mitochondrial cytochrome C oxidase subunit‐I ( coi‐I ) gene. The ALS cell line had the maximum growth rate in DMEM/F‐12 medium containing 20% FBS at 27°C. Chromosome number analysis showed that the ALS cells have a modal diploid chromosome number of 34. The ALS cell line was transfected with the pEGFP‐N1 plasmid, and green fluorescence was observed. The ALS cell line was used for testing Mandarinfish ranavirus (MRV) susceptibility, and the cytopathic effects in the cell line were observed at 4 days post‐infection (dpi). Furthermore, the susceptibility of the ALS cell line to MRV and the levels of MRV mRNA and viral loads were found to be significantly increased at 1–7 dpi. This study revealed that the ALS cell line could be useful for molecular, virological, and biotechnological studies on yellowfin seabream.